High seroprevalence of SARS-CoV-2 in cats linked to human infection in a Latin American country with elevated COVID-19 transmission and mortality - Ulloa, Alexandra; Cordero-Ortiz, Maritza; Jara, Luis M.; Schiaffino, Francesca; Ferradas, Cusi; Sánchez-Carrión, Camila; Martínez-Vela, Ana; Hernández, Jesús; Giménez-Lirola, Luis G. (Frontiers in Veterinary Science, 2025)
IntroductionSARS-CoV-2 has been shown to infect various animal species, including companion animals such as cats. Although direct transmission from cats to humans has not been confirmed, monitoring the prevalence of infection in these animals remains critical as susceptible hosts to SARS-CoV-2, particularly in regions with high COVID-19 case numbers. This study aimed to evaluate the seroprevalence of SARS-CoV-2 in cats during the first wave of the COVID-19 pandemic in Lima, Peru.MethodsSerum samples from 544 cats, collected between 2020 and 2021, were tested for antibodies using a double antigen sandwich ELISA targeting the receptor-binding protein domain (RBD) and the nucleocapsid (N) proteins. This ELISA has a sensitivity of 80% and a specificity of 100%.ResultsA seroprevalence of 43.8% was observed, with higher rates in females (63.9%), kittens (51.3%), and the Domestic Shorthair breed (93.2%). Among owners diagnosed with COVID-19, 95.5% of their cats were seropositive, with no cross-reactivity observed for other common feline diseases.ConclusionThese findings suggest significant SARS-CoV-2 exposure and possible infection in cats during the early pandemic phase in Peru. The high seroprevalence observed highlights the need for ongoing surveillance of companion animals, especially in regions with high human infection rates.